1984
DOI: 10.1007/bf00230075
|View full text |Cite
|
Sign up to set email alerts
|

The lactose synthase acceptor site: a structural map derived from acceptor studies

Abstract: A pictorial map of the lactose synthase (galactosyl transferase) acceptor binding site has been formulated from this and published studies on substrate analogs and inhibitors. The basic requirements are a pyranose, thiopyranose or inositol ring structure and equatorial substituents (if any) at C-2, C-3, C-4, and C-5. The aglycone (at C-1) may be either alpha or beta-, but alpha- is somewhat preferred. In the absence of alpha-lactalbumin galactosyl transferase will accept long chain 2-N-acyl substituents on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…2125 Neisseria meningitidis β4GalT (NmLgtB) and Helicobacter pylori β4GalT (Hpβ4GalT), and Bβ4GalT have been used broadly for enzymatic and chemoenzymatic synthesis of β1–4-linked galactosides. 13, 21, 2630 NmLgtB has been fused with a Streptococcus thermophilus UDP-galactose 4-epimerase (NmLgtB-StGalE) to allow the use of a less expensive sugar nucleotide uridine 5'-disphosphate glucose (UDP-Glc) as the starting material which can be converted to uridine 5'-disphosphate galactose (UDP-Gal) by StGalE for NmLgtB-catalyzed synthesis of β1–4-linked galactosides. 31 Although the tolerance of the modifications on the acceptor substrates of β4GalTs has been tested using monosaccharide derivatives, 21, 32 their tolerance of modifications on longer oligosaccharides such as trisaccharides is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…2125 Neisseria meningitidis β4GalT (NmLgtB) and Helicobacter pylori β4GalT (Hpβ4GalT), and Bβ4GalT have been used broadly for enzymatic and chemoenzymatic synthesis of β1–4-linked galactosides. 13, 21, 2630 NmLgtB has been fused with a Streptococcus thermophilus UDP-galactose 4-epimerase (NmLgtB-StGalE) to allow the use of a less expensive sugar nucleotide uridine 5'-disphosphate glucose (UDP-Glc) as the starting material which can be converted to uridine 5'-disphosphate galactose (UDP-Gal) by StGalE for NmLgtB-catalyzed synthesis of β1–4-linked galactosides. 31 Although the tolerance of the modifications on the acceptor substrates of β4GalTs has been tested using monosaccharide derivatives, 21, 32 their tolerance of modifications on longer oligosaccharides such as trisaccharides is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gal-T1, the milk galactosyltransferase enzyme transfers Gal to the non-reducing terminal N-acetylglucosamine (GlcNAc) residue of glycans to form ␤-1,4-linked galactosylated glycan and to free GlcNAc to form N-acetyllactosamine (1), whereas Gal-T6 transfers Gal to Glc in glucosylceramide synthesizing lactosylceramide (10). Gal-T1 has been reported to be able to use, at a lower efficiency, other N-acetyl/N-acyl substituted sugars such as N-acetyl-D-mannosamine, N-acetylmuramic acids as sugar acceptors (11). It also does not show an absolute requirement for UDP-Gal as a sugar donor since it can transfer glucose (Glc), 2-deoxy-Glc, arabinose, and GalNAc from their UDP derivatives, albeit at very low efficiencies (12)(13)(14).…”
mentioning
confidence: 99%
“…In fact, our results can be compared to the classical studies by Brew et al [40] which indicated 85% inhibition of the LacNAc synthesis at 2 mg ml Ϫ1 (140 lM) a-LA. On the other hand, Berliner et al [42] demonstrated a 100% activation of bovine b4GalT1 in the presence of 0.4 mg ml Ϫ1 (30 lM) a-LA and 2 mM GlcNAc. In this study it was also stated that the enzymatic conversion of glucosamine acceptors carrying longer N-acyl chains (e.g., N-octanoyl-) is inhibited by a-LA concluding that a-LA binds to a hydrophobic region of b4GalT1 and that both binding sites are juxtaposed.…”
Section: Effect Of A-lactalbumin and Substrate Specificitymentioning
confidence: 97%